Paroxetine reduces crying in young women watching emotional movies - van der Veen, Frederik M. (Springer-Verlag, 2011)
RATIONALE: Crying is a unique human emotional reaction that has not received much attention from researchers. Little is known about its underlying neurobiological mechanisms, although there is some indirect evidence suggesting the involvement of central serotonin. OBJECTIVES: We examined the acute effects of the administration of 20 mg paroxetine on the crying of young, healthy females in response to emotional movies. METHODS: We applied a double-blind, crossover randomised design with 25 healthy young females as study participants. On separate days, they received either paroxetine or placebo and were exposed to one of two emotional movies: ‘Once Were Warriors’ and ‘Brian’s Song’. Crying was assessed by self-report. In addition, the reactions to emotional International Affective Picture System (IAPS) pictures and mood were measured. RESULTS: Paroxetine had a significant inhibitory effect on crying. During both films, the paroxetine group cried significantly less than the placebo group. In contrast, no effects on mood and only minor effects on the reaction to the IAPS pictures were observed. CONCLUSIONS: A single dose of paroxetine inhibits emotional crying significantly. It is not sure what the underlying mechanism is. However, since there was no effect on mood and only minor effects on the response to emotional pictures, we postulate that paroxetine mainly acts on the physiological processes involved in the crying response.